2013
DOI: 10.1177/0093854813494183
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prior Relationship on Perceptions of Stalking

Abstract: The current research examined the influence of prior relationship on perceptions of stalking, and compared the perceptions of laypersons, nonspecialist police officers, and specialist police officers. Two studies employed experimental designs where participants were presented with one of three vignettes in which the nature of the prior relationship was manipulated so that the perpetrator and victim were portrayed as strangers, acquaintances, or ex-partners. Participants comprised 101 nonspecialist police offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
(75 reference statements)
2
21
0
1
Order By: Relevance
“…Despite this evidence, ex-partners are less likely to be convicted of stalking and cases of harassment are more likely to be dropped when the harassment involves an expartner rather than a stranger (Harris, 2000). Further, Scott and Gavin (2011) found that mock jurors were more likely to reach a guilty verdict when the perpetrator was portrayed as a stranger rather than an ex-partner. Evidently, preconceived ideas about the nature of stalking which are not reflective of the realities of the behaviour impact on decision making and criminal justice responses.…”
Section: Introductionmentioning
confidence: 92%
“…Despite this evidence, ex-partners are less likely to be convicted of stalking and cases of harassment are more likely to be dropped when the harassment involves an expartner rather than a stranger (Harris, 2000). Further, Scott and Gavin (2011) found that mock jurors were more likely to reach a guilty verdict when the perpetrator was portrayed as a stranger rather than an ex-partner. Evidently, preconceived ideas about the nature of stalking which are not reflective of the realities of the behaviour impact on decision making and criminal justice responses.…”
Section: Introductionmentioning
confidence: 92%
“…This may reflect previous findings that knowledge of or exposure to stalking may reduce endorsement of some stalking myths. Weller et al (2013) and Scott et al (2013) both found that police with specialist training or direct experience of stalking cases endorsed fewer misperceptions about stalking, took stalking more seriously and were less likely to blame victims. Unfortunately, a firm conclusion about whether police took stalking more seriously than community members due to additional knowledge cannot be drawn as such knowledge was not assessed in this study.…”
Section: Between Group Differences In Stalking Myth Endorsementmentioning
confidence: 98%
“…When presented with short stalking vignettes in which the prior relationship between victim and stalker is manipulated, all respondents, whether male or female, general community or police officers, are more likely to identify unwanted intrusions by strangers as stalking. Strangers are also judged to present a greater threat and require more police response than ex-partners or acquaintances (Hills & Taplin, 1998;Phillips, Quirk, Rosenfeld, & O'Connor, 2004;Scott, Lloyd, & Gavin, 2010;Scott, Nixon, & Sheridan, 2013;Scott et al, 2014;Sheridan, Gillett, Davies, Blaauw, & Patel, 2003;Weller, Hope, & Sheridan, 2013). Recent research by Scott and colleagues (2013) and Weller and colleagues (2013) demonstrates that even among police who have specialist training or direct experience with stalking cases, stranger stalkers are viewed as more problematic or a greater threat.…”
Section: Perceptions Of Stalkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no research has investigated the aforementioned in terms of CSA victims, similar research has been conducted within the stalking literature and revealed specialist police officers to be less influenced by stalking myths compared to non-specialist police officers (Scott, Nixon, & Sheridan, 2013). Therefore, evaluating whether such differences are prevalent in terms of CSA victims is deemed important to identify training needs and in turn improve the support provided to CSA victims.…”
Section: Further Researchmentioning
confidence: 99%